An exploratory study of English language teachers’ perspective on social-emotional learning in ESL classrooms in Malaysian primary schools - Timothy James, Joamchimdass (2022)

(untitled)
English Lessons in Malaysian primary schools prioritise on cognitive learning mainly through textbooks. However, Social-emotional learning (SEL) that helps promote a comfortable and fun learning environment for students to express emotions, build relationships, and making ethical decisions seems to be neglected in Malaysian ESL classrooms. Therefore, this study focused on primary school English teachers’ perspective on SEL by identifying challenges faced and possible ways to integrate SEL effectively into their English lessons. A qualitative research approach using phenomenology was employed. Using the purposive sampling technique, six primary school English teachers from Perak were identified and interviewed. Thematic analysis was then employed. The study found more external challenges such as culture, lack of resources and time compared to internal challenges, knowledge. Possible ways showed patterns among relationships, methods, teacher roles, environment, and syllabus. Findings commonly linked to competence and relatedness as opposed to autonomy using the Self-Determination Theory. Furthermore, to handle SEL techniques in an English Language classroom, instructors must be prepared. This study hopes to create awareness among teachers and allow policy makers to give teachers professional SEL training. Lastly, other methods, participants and theories should also be explored to show a possibility of SEL integration in ESL classrooms.